Laparoscopic gastric dissociation using a two-port approach in minimally invasive esophagectomy - Huaguang Pan; Renquan Zhang; Ao Li; Hanlin Fang; Hao Zheng; Menglong Jiang; Wei Ge; Fan Zhou; Xiancheng Liu; Chuntong Yin (World Journal of Surgical Oncology, 2022)
Abstract Background A new approach for laparoscopic gastric dissociation in minimally invasive esophagectomy (MIE) was attempted. This study aimed to evaluate the short-term outcomes, safety, and efficacy of two-port laparoscopy using the McKeown procedure. Methods This retrospective study included 206 consecutive patients with esophageal cancer who underwent a modified two-port laparoscopic or the traditional five-port McKeown procedure at our institution from August 2019 to August 2021. Surgical outcomes of the two methods were compared. Results Of the 206 patients, 106 (51.46%) underwent the modified two-port procedure, whereas 100 (48.54%) underwent the traditional five-port procedure. Subsequently, 182 propensity score-matched patients were compared. No significant differences were observed in laparoscopic operative time, blood loss during laparoscopic surgery, number of dissected lymph nodes, and pain score on postoperative day 1 between the two groups. The rate of complication and postoperative length of hospital stay did not differ significantly between the two groups. The total hospitalization cost also did not differ significantly between the two groups (p = 0.325). No postoperative deaths occurred in either group. Conclusions Our findings demonstrate that laparoscopic gastric dissociation using the two-port approach in MIE is a safe and effective procedure, with short-term outcomes comparable to those of the traditional five-port procedure in patients with esophageal cancer. Larger studies with longer follow-up duration are warranted.